Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Pegawai Pada Balai Besar Meteorologi, Klimatologi Dan Geofisika Wilayah IV Makassar - Amalia Amalia (SEIKO : Journal of Management & Business, 2023)
This study aims to determine the effect of compensation and work motivation on employee performance at the Makassar Region IV Meteorology, Climatology and Geophysics Center. This type of research is quantitative using saturated sample techniques as many as 73 employees as respondents with data analysis techniques using multiple liner regression analysis. The results showed that; (i) compensation directly affects employee performance, (ii) motivation directly affects employee performance, and (iii) compensation and motivation simultaneously affect employee performance. Keywords: compensation, motivation, employee performance